경상북도 골재수요-공급 관리 전략 연구 - 이진영(Jin-Young Lee); 홍세선(Sei Sun Hong); 백철승(Chul Seoung Baek) (자원환경지질, 2024)
Aggregate typically refers to sand and gravel formed by the transportation of rocks in rivers or artificially crushed, constituting a core resource in the construction industry. Gyeongsangbuk-do, the largest administrative area in South Korea, produces various sources of gravel, including forest, land (excluding other sources), river, and crushed stone. As of 2022, it has extracted approximately 6.96 million cubic meters of aggregate, with permitted production totaling around 4.07 million cubic meters and reported production of about 2.88 million cubic meters. The aggregate demand in Gyeongsangbuk-do is estimated to be 12.39 million cubic meters according to the estimation method in Ready-Mix Concrete. From the supply perspective, about 120 extraction sites are operational, with most municipalities maintaining an appropriate balance between aggregate demand and supply. However, in some areas, there is inbound and outbound transportation of aggregate to neighboring regions. Regions with significant inbound and outbound aggregate transportation in Gyeongsangbuk-do are areas connected to Daegu Metropolitan City and Pohang City along the Gyeongbu rail line, showing a high correlation with population distribution. Gyeongsangbuk-do faces challenges such as population decline, aging rural areas, and insufficient balanced regional development. Analysis using GIS reveals these trends in gravel demand and supply. Currently in this study, Gyeongsangbuk-do meets its demand for aggregate through the supply of various aggregate sources, maintaining stable aggregate procurement. River and terrestrial aggregates may be sustained as short-term supply strategies due to the difficulty of longterm development. Considering the reliance on raw material supply for selective crushing, it suggests the need for raw material management to maintain stability. Gyeongsangbuk-do highlights quarries in the forest as an important resource for sustainable aggregate supply, advocating for the development of large-scale aggregate quarries as a long-term alternative. These research findings are expected to provide valuable insights for formulating strategies for sustainable management and stable utilization of aggregate resources. 골재는 일반적으로 암석이 강에서 운반되거나 인공적으로 파쇄되어 형성된 모래와 자갈 등을 말하며, 건설 산업의 핵심 자원이다. 경상북도는 전국에서 가장 넓은 행정구역으로, 산림골재, 육상골재, 하천골재, 선별파쇄골재 등 다양한 종류의 골재를 생산하고 있다. 2022년 기준으로 약 696 만m3의 골재를 채취하였으며, 이 중 허가에 의한 채취물량은 약 407 만m3, 신고물량은 약 288 만m3이다. 경상북도의 골재수요는 레미콘 공급량의 추정 방법에 따라 1,239 만m3로 나타난다. 골재의 공급 측면에서는 약 120 개의 채취장이 운영되고 있으며, 대부분의 시군에서는 골재의 수요와 공급이 적절하게 유지되고 있다. 다만, 일부 지역에서는 경상북도 인접지역에 반입과 반출이 발생하고 있다. 경상북도의 골재의 반입과 반출이 많은 지역은 경부선을 따라 경상북도 남부와 대구광역시, 포항시로 연결되는 지역이며 인구의 분포와 높은 관련성이 나타난다. 경상북도는 인구 감소와 농촌 지역의 고령화, 지역 간의 균형 발전 부족 등의 문제에 직면하고 있으며, 연구결과로 제시된 GIS를 이용하여 출발지-도착지 분석을 통해 파악된 골재의 수요와 공급 흐름에서도 이러한 양상이 확인된다. 경상북도의 골재산업구조와 공간구조를 분석한 결과 현재 경상북도는 다양한 골재원의 공급으로 수요를 충족하고 안정적인 골재 수급이 유지되고 있다. 하천골재와 육상골재는 장기적인 개발이 어렵기 때문에 단기간 공급전략으로 유지될 수 있으며, 선별파쇄를 통한 공급은 원석 공급에 의존하여 안정성 유지가 어려운 상황을 고려하여 원석관리의 필요성을 제안하였다. 경상북도에서는 골재자원의 안정적 공급을 위한 장기적인 대안으로 산림골재가 중요 자원으로 부각되어 대규모 골재 채석장 개발의 필요성을 제시하였다. 본 연구결과는 골재 자원의 지속 가능한 관리와 안정적 활용을 위한 전략 수립에 중요한 정보를 제공할 것으로 기대된다.